Albugo candida race diversity, ploidy and host‐associated microbes revealed using DNA sequence capture on diseased plants in the field. Issue 3 (5th October 2018) - Jouet, Agathe; Saunders, Diane G. O.; McMullan, Mark; Ward, Ben; Furzer, Oliver; Jupe, Florian; Cevik, Volkan; Hein, Ingo; Thilliez, Gaetan J. A.; Holub, Eric; van Oosterhout, Cock; Jones, Jonathan D. G.
Summary: Physiological races of the oomycete Albugo candida are biotrophic pathogens of diverse plant species, primarily the Brassicaceae, and cause infections that suppress host immunity to other pathogens. However, A. candida race diversity and the consequences of host immunosuppression are poorly understood in the field. We report a method that enables sequencing of DNA of plant pathogens and plant‐associated microbes directly from field samples (Pathogen Enrichment Sequencing: PenSeq). We apply this method to explore race diversity in A. candida and to detect A. candida ‐associated microbes in the field (91 A. candida ‐infected plants). We show with unprecedented resolution that each host plant species supports colonization by one of 17 distinct phylogenetic lineages, each with an unique repertoire of effector candidate alleles. These data reveal the crucial role of sexual and asexual reproduction, polyploidy and host domestication in A. candida specialization on distinct plant species. Our bait design also enabled phylogenetic assignment of DNA sequences from bacteria and fungi from plants in the field. This paper shows that targeted sequencing has a great potential for the study of pathogen populations while they are colonizing their hosts. This method could be applied to other microbes, especially to those that cannot be cultured. Abstract : See also the Commentary on this article by Kale, 221 : 1177–1179.